The relationship between trading volume, returns and volatility in the Kuala Lumpur Stock Exchange - Izani Ibrahim,; Yaccob Othman, (Penerbit Universiti Kebangsaan Malaysia, 2000)
This paper presents an empirical analysis of the relationship between trading volume, returns and volatility on the Main Board of Kuala Lumpur Stock Exchange. The findings in this paper help to explain how returns are generated and the implications for inferring return behavior from trading volume data. It provides evidence for the positive relationship between trading volume and volatility. The asymmetric relationship which is hypothesised to exist due to the differential cost of taking long and short positions is evident through the smaller slope for negative return in the volume-price change relationship. This paper also studies the relationship at individual stock level. Consistent with the belief of non-normality in returns (and ARCH effects) through the rate of arrival of information, the study shows that there is a reduction in the significance and magnitude of persistence in volatility